Exploring the knowledge and attitude of medical and pharmacy students about generic medicine in Lahore, Pakistan. (March 2018) - Asif, Usama; Saleem, Zikria; Yousaf, Mahrukh; Saeed, Hamid; Hashmi, Furqan Khurshid; Hassali, Mohamed Azmi
Background: The age of out-of-pocket health-care expenditures demands the practice of generic medicine. Our objective was to evaluate the knowledge and attitude about generic medicine among medical and pharmacy students of Lahore, Pakistan. Methods: A cross-sectional study was performed among calculated sample size (via online Raosoft calculator) of 295 students including 185 pharmacy and 110 medical students from third, fourth, and final year of studies using convenient sampling approach. A pre-validated questionnaire was used to assess the knowledge of students regarding generic medicine. Data were analyzed using SPSS version 20. Results: We found that a majority of both pharmacy and medical students were aware of the meaning of brand and generic medicine where 86 (29.7%) students believed that generic medicine is bioequivalent to brand name product and 108 (36.5%) students agreed that cost burden will be reduced with the use of generics. There were concerns about quality (P ≤ 0.05) and side effects (P ≤ 0.005) of generic medicine as compared to brands. Significant associations were found between the knowledge of medical and pharmacy students (P ≤ 0.005). Conclusion: Educational interventions and policies regarding generic medicine practices are strongly needed to overcome the knowledge deficits among pharmacy and medical students.